Assessing motivation orientations in schizophrenia: Scale development and validation. Issue 1 (30th January 2015) - Cooper, Shanna; Lavaysse, Lindsey M.; Gard, David E.
Abstract: Motivation deficits are common in several disorders including schizophrenia, and are an important factor in both functioning and treatment adherence. Self-Determination Theory (SDT), a leading macro-theory of motivation, has contributed a number of insights into how motivation is impaired in schizophrenia. Nonetheless, self-report measures of motivation appropriate for people with severe mental illness (including those that emphasize SDT) are generally lacking in the literature. To fill this gap, we adapted and abbreviated the well-validated General Causality Orientation Scale for use with people with schizophrenia and with other severe mental disorders (GCOS-clinical populations; GCOS-CP). In Study 1, we tested the similarity of our measure to the existing GCOS (using a college sample) and then validated this new measure in a schizophrenia and healthy control sample (Study 2). Results from Study 1 ( N =360) indicated that the GCOS-CP was psychometrically similar to the original GCOS and provided good convergent and discriminant validity. In Study 2, the GCOS-CP was given to individuals with ( N =44) and without schizophrenia ( N =42). In line with both laboratory-based and observer-based research, people with schizophrenia showed lower motivational autonomy and higher impersonal/amotivated orientations. Additional applications of the GCOS-CP are discussed. Highlights: The GCOS-CP was psychometrically similar to the GCOS. People with and without schizophrenia were more autonomy oriented than control or amotivated oriented. Individuals with schizophrenia showed higher amotivation than those without schizophrenia. Individuals with schizophrenia had lower autonomy orientation than those without schizophrenia. No group differences were found in control orientation.